STRATEGI KETERCAPAIAN KETERWAKILAN PEREMPUAN DALAM PEMILIHAN LEGISLATIF KOTA TANJUNGPINANG PERIODE 2019-2024 - Mowong, Lavionita Gerciani; Kustiawan, Kustiawan; Winarti, Novi (Regalia: Jurnal Riset Gender dan Anak, 2025)
Based on Law No. 7 of 2017 concerning Political Parties, and Law No. 10 of 2008 concerning General Elections which states that include at least 30% of women's representation in legislative elections and in the management of political parties. In this case, the government has provided opportunities and efforts in fulfilling representation in women, but in fact there are still many factors related to women's participation in politics which makes women's positions less viewed in terms of politics so that with this regulation it is hoped that women can get their rights and also have enthusiasm in politics, especially in the legislature. In the Tanjungpinang City legislative election for the 2019 period, there were ten (10) political parties that succeeded in positioning female legislative candidates, so that the calculation of female DPRD members in the 2019-2024 period reached eleven (11) people with a total percentage of 36.67%. Therefore, this study aims to find out how the Strategy for Achieving Women's Representation in the Tanjungpinang City Legislative Election for the 2019-2024 Period. then there is a strategy carried out by the winning political party and also of course there is a movement of strategies per individual or legislative candidates who apply their own strategies in the legislative elections. In fulfilling the representation of women during the legislative elections, there is a theory of political strategy proposed by Peter Schrorder. Where the theory is such as the theory of situation analysis, strategy control, strategy implementation, strategy formulation and strategy evaluation. From this theory, strategies and implementation will be obtained carried out by the winning political party in achieving the representation of women.